Pengaruh Limbah Solid dan NPK Tablet TerhadapPertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq.)di Pembibitan Utama - Theonanta Ginting; Elza Zuhry; Adiwirman Adiwirman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The research aimed to know the effect of solid waste and  tablet NPK on the growth of oil palm seedlings in the main nursery. The experiment was conducted in the experimental station of Agricultural Faculty of Riau University from April to August 2016. The research used Factorial Completely Randomized Design (RAL) consisting 2 factor. The first factor of solid waste was 0, 10 and 20 g/plant and the second factor of tablet NPK was 0, 25 and 50 g/plant. Data have been statistically analized and examined further with BNJ if significant effect on level 5%. The outcomes indicated that there was interaction between solid waste and tablet NPK on height of seed , leaf area, number of leaf, diameter of the hump, development of leaf area, volume of root and ratio of root canopy (RTA) palm oil plant. Giving of 4 ton/ha solid waste and 10 ton/ha tablet NPK gives the best growth and development of palm oil seeds. Keywords: Solid Waste, Tablet NPK, Palm Oil Seedlings.